Pharmacoepidemiological Study of the Use of Antibacterial Agents in the Multi-Speciality Hospitals of St. Petersburg - S. V. Sidorenko; A. S. Kolbin; S. A. Shlyapnikov; A. M. Kuzhel; A. V. Repina; Yu. V. Lobzin; N. N. Klimko; P. K. Yablonsky; V. A. Mazurov; A. V. Shchegolev; A. V. Rudakova; A. R. Danilchenko; et al. (Антибиотики и Химиотерапия)
At the initiative of the St. Petersburg's Territorial Fund for Mandatory Medical Insurance a retrospective cross-sectional observational study of the structure and adequacy of antibiotic use was initiated in four multi-specialty hospitals in the city (with a total bed capacity of more than 4 thousand) in 2014. In total, 18,250 medical records of the inpatients were analyzed, of which 2008 cards of the patients receiving antibiotics were selected, the CRFs were filled in according to the selected cards. Subsequently, 1978 of the 2008 CRFs were included in the detailed analysis after the final verification of the electronic database. Of the 1978 antibiotic prescriptions, a microbiological study was assigned in 585 (28%). Each patient received an average of 1.9 courses of antibiotics. In general, the therapy duration was up to two weeks. Short courses (from 1 to 5 days) were prescribed in 51% of cases, in 40% of cases the duration of therapy ranged from 6 to 14 days. Only 9% had to take antibiotics for more than 2 weeks. A total of 60 different antibiotics were used. Ceftriaxone, metronidazole, ciprofloxacin, cefazolin, and cefotaxime accounted for 78% of prescriptions. The most commonly prescribed combination therapy used 2 antibacterial drugs. Perioperative prophylaxis in surgery accounted for 22% of prescriptions, antibiotics were prescribed for the purpose of empirical therapy in 67% of cases. Targeted therapy accounted for only 7% of the total number of medical prescriptions. The duration of primary antibiotic prophylaxis in surgery was up to 24 hours only in 14% of the cases. Adequate antibiotic therapy was prescribed in 26% of the cases of acute pyelonephritis and in 31% of the cases of community-acquired pneumonia. Antibiotics were prescribed in the absence of the signs of bacterial infection documented in the medical history in 35% of the cases. There is an obvious need to take urgent measures to optimize the practice of antibiotic therapy in hospitals of St. Petersburg.